A sociological study of alienation - Bekker, Ann Michaud (Department of Sociology, 2023)
The aim of this study is to illuminate the problems which arise in seeking to test Marx's theory of alienation empirically, and to assess the contributions of empirical studies of alienation to circumvent some of these problems. Firstly, a framework is constructed to analyse different theories of alienation. Next, Marx's theory is so analysed, as well as a ruler of other empirical studies. This theory and these studies are critically assessed. In conclusion, it is shown that Marx's theory needs elaboration especially with regard to the conception of 11 class consciousness". Empirical studies of this theory, moreover, tend to be either too confined in theoretical scope, on the one hand, or too divergent from the basic Marxist approach, on the other.